The Role of miRNAs as New Molecular Biomarkers for Dating the Age of Wound Production: A Systematic Review - De Simone, Stefania; Giacani, Elena; Bosco, Maria Antonella; Vittorio, Simona; Ferrara, Michela; Bertozzi, Giuseppe; Cipolloni, Luigi; La Russa, Raffaele (Frontiers in Medicine, 2022)
Background: The timing of wounds production is a significant issue in forensic pathology. Although various methods have been evaluated, obtaining an accurate dating of lesions is still a challenge. The pathologist uses many parameters to value wound age, such as histological and immunohistochemical. In recent years, there have been many studies regarding the use of miRNAs in wound-age estimation; indeed, miRNAs have multiple potential uses in forensic pathology. Scope: This review aims to verify the efficacy and feasibility of miRNAs as a tool for determining the timing of lesions. Materials and Methods: The authors conducted the systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. PubMed was used as a search engine to find articles published between January, 1st 2016 and October, 1st 2021, to evaluate the current state of the art regarding wound-age estimation. Results: A total of 256 articles were collected; after screening according to PRISMA guidelines, the systematic review included 8 articles. The studies included in this review were all Original articles evaluating the use of biomarkers for wound-age determination. Discussion and Conclusion: The literature review showed that analysis of miRNA is an innovative field of study with significant potentiality in forensic pathology. There are few studies, and almost all of them are at an early stage. The challenge is to understand how to standardize the samples' selection to obtain reliable experimental data. This observation represents a necessary prerequisite to planning further clinical trials.